2019
DOI: 10.3389/fgene.2019.00503
|View full text |Cite
|
Sign up to set email alerts
|

Minigene Splicing Assays Identify 12 Spliceogenic Variants of BRCA2 Exons 14 and 15

Abstract: A relevant fraction of BRCA2 variants is associated with splicing alterations and with an increased risk of hereditary breast and ovarian cancer (HBOC). In this work, we have carried out a thorough study of variants from BRCA2 exons 14 and 15 reported at mutation databases. A total of 294 variants from exons 14 and 15 and flanking intronic sequences were analyzed with the online splicing tools NNSplice and Human Splicing Finder. Fifty-three out of these 294 variants were selected as cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Three previously characterized ESE variants, c.8378G>A (exon 19), c.8969G>A (exon 23), and c.9006A>T (exon 23) (Acedo et al, 2012), lie within microdeletions shown to impact mRNA splicing, thereby demonstrating the utility of this strategy to locate putative ESE variants (Acedo et al, 2015). Fraile‐Bethencourt et al adapted this systematic minigene assay approach to map active ESEs in BRCA2 exons 2–9 and 14–18 (Fraile‐Bethencourt et al, 2017; Fraile‐Bethencourt, Valenzuela‐Palomo, Díez‐Gómez, Acedo, & Velasco, 2018; Fraile‐Bethencourt, Valenzuela‐Palomo, Díez‐Gómez, Caloca, et al, 2019; Fraile‐Bethencourt, Valenzuela‐Palomo, Díez‐Gómez, Goina, et al, 2019). Selection of variants within the microdeletion‐mapped ESEs improved the specificity of bioinformatic predictions (Fraile‐Bethencourt, Valenzuela‐Palomo, Díez‐Gómez, Goina, et al, 2019).…”
Section: Experimental Assays Can Identify Active Exonic Sres: Brca1/2mentioning
confidence: 99%
“…Three previously characterized ESE variants, c.8378G>A (exon 19), c.8969G>A (exon 23), and c.9006A>T (exon 23) (Acedo et al, 2012), lie within microdeletions shown to impact mRNA splicing, thereby demonstrating the utility of this strategy to locate putative ESE variants (Acedo et al, 2015). Fraile‐Bethencourt et al adapted this systematic minigene assay approach to map active ESEs in BRCA2 exons 2–9 and 14–18 (Fraile‐Bethencourt et al, 2017; Fraile‐Bethencourt, Valenzuela‐Palomo, Díez‐Gómez, Acedo, & Velasco, 2018; Fraile‐Bethencourt, Valenzuela‐Palomo, Díez‐Gómez, Caloca, et al, 2019; Fraile‐Bethencourt, Valenzuela‐Palomo, Díez‐Gómez, Goina, et al, 2019). Selection of variants within the microdeletion‐mapped ESEs improved the specificity of bioinformatic predictions (Fraile‐Bethencourt, Valenzuela‐Palomo, Díez‐Gómez, Goina, et al, 2019).…”
Section: Experimental Assays Can Identify Active Exonic Sres: Brca1/2mentioning
confidence: 99%
“…For many BRCA1 and BRCA2 variants (both intronic and exonic) an effect on mRNA splicing has been reported using either patient RNA or minigene analysis. [12][13][14][15][16][17][18][19][20][21] The analysis of patient RNA is however often hampered by the inability to determine allele-specific transcript expression. It then remains unclear if and to what extent wild type (WT) mRNA is still produced from the variant allele.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this construct was fully functional and induced a full-length transcript of the expected size and sequence (Figures 2B,C). Likewise, the mutant constructs (c.864+5G>T and c.996+2_996+5del) yielded clean splicing patterns (Figure 2C), where three aberrant transcripts [ (E1q141), (E2), and (E2q135)] were identified with high resolution and sensitivity by fluorescent fragment analysis (Fraile-Bethencourt et al, 2019a). Thus, c.864+5G>T induced a deletion of 141 nt of exon 1, similar to previously reported variant c.864+1G>C (Gantla et al, 1998), but also a significant proportion of the full-length transcript (29.6%) (Figures 2B-E).…”
Section: Discussionmentioning
confidence: 95%
“…Variants and transcripts were described according to the Human Genome Variation Society (HGVS) guidelines on the basis of the UGT1A1 GenBank sequence NM_00463.2. For simplification, transcripts were annotated with a shortened code, as described previously (Fraile-Bethencourt et al, 2019a;Lopez-Perolio et al, 2019):…”
Section: Variant Nomenclaturementioning
confidence: 99%